2009
DOI: 10.1111/j.1095-8312.2009.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Automictic parthenogenesis of a geographically parthenogenetic mayfly, Ephoron shigae (Insecta: Ephemeroptera, Polymitarcyidae)

Abstract: In the geographically parthenogenetic mayfly, Ephoron shigae, egg maturation and counts of chromosome number of unfertilized, parthenogenetic eggs were studied, in comparison with fertilized eggs from a bisexual population. The primary oocyte becomes mature through two successive maturation divisions. The first maturation division (meiotic division) takes place in the primary oocyte to produce a secondary oocyte and a first polar body. The second maturation division soon occurs in the secondary oocyte, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…A difference of karyological characters in both species, E. shigae and E. eophilum , also strongly supports molecular phylogeny. In previous studies of E. shigae , the numbers of chromosomes were 2 n = 12 (female) and 2 n = 11 (male), and the sex chromosomes exhibited an XX (female) and XO (male) pattern (Sekiné & Tojo, , 2010a, b). In the present study of E. eophilum , the numbers of chromosomes were mainly shown to be 2 n = 15 and 16 (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A difference of karyological characters in both species, E. shigae and E. eophilum , also strongly supports molecular phylogeny. In previous studies of E. shigae , the numbers of chromosomes were 2 n = 12 (female) and 2 n = 11 (male), and the sex chromosomes exhibited an XX (female) and XO (male) pattern (Sekiné & Tojo, , 2010a, b). In the present study of E. eophilum , the numbers of chromosomes were mainly shown to be 2 n = 15 and 16 (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Upon hatching of the nymphs having soft cuticle and little yolk within the abdomen, chromosome preparations were made and chromosomes were counted for each specimen, in accordance with the method of our previous study (Sekiné & Tojo, 2007, 2010a, b). The whole nymphs (body length < 1 mm) were prepared on slides by wounding the tissue with a needle and forceps and incubating for 30 min in ion‐exchange water containing 0.005% colcemide.…”
Section: Methodsmentioning
confidence: 99%
“…In E. shigae , Sekiné & Tojo (2007, 2009) indicate that all parthenogenetic offspring from the unisexual populations were female (2 n = 12), and that the reproductive mode of the unisexual populations can be described as diploid thelytokous parthenogenesis. These results also indicate that all of the parthenogenetic offspring from bisexual population are female (2 n = 12; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…, 2006). Furthermore, it is revealed that all individuals reproduced by parthenogenesis are diploid females (2 n = 12), indicating the occurrence of thelytokous parthenogenesis (Sekiné & Tojo, 2007, 2009). However, the parthenogenetic ability of females in bisexual populations has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies on Ephoron shigae (Takahashi, 1924) (Polymitarcyidae) demonstrated automictic diploid thelytoky (Sekiné and Tojo , ,b; Sekiné et al. ).…”
Section: Insecta (=Ectognatha)mentioning
confidence: 99%